Effect of the compatilizer and chemical treatments on the performance of poly(lactic acid)/ramie fiber composites. (October 2021) - Zhan, Jianghu; Wang, Guilong; Li, Jiao; Guan, Yanjin; Zhao, Guoqun; Naceur, Hakim; Coutellier, Daniel; Lin, Jun
Abstract: Natural fiber composites are of great potential for renewability and environmental friendless, but the poor interfacial bonding between the fiber and polymer matrix limits its engineering applications. In the present study, the mechanical strength of the poly (lactic acid) (PLA)/ramie fiber composites were focused. The adhesion ability was investigated by adding the compatilizer triglycidyl isocyanurate (TGIC) or treating the fibers with silane, NaOH or the combination of NaOH and silane. Fourier transform infrared spectroscopy analysis showed that PLA molecular chain was bonded on the fiber surface after treating the fibers or blending with TGIC, resulting in many tore and broke fibers in the fracture surface of the composits. At the same time, the rheological analysis indicated that the viscoelastic response of the composites was improved since the mobility of the PLA molecular chains were restricted in composites. In addition, the tensile and flexural strengths of the composites were significantly improved by the fiber surface treatment and blending with TGIC. Especially, the introduction of untreated fibers and TGIC in PLA increased the tensile and flexural strengths by 49.8% and 46.5%, respectively. Highlights: Chemical modifications removed the impurities of the fiber surface and enhanced the wettability and the mechanical properties of PLA/ramie fiber composites. Incorporation of compatilizer TGIC increased the tensile and flexural strengths by 49.8% and 46.5%, respectively.anys were torn and broken in the matrix. Surface modifications and TGIC addition connected the PLA molecular chain on the fiber surface and improved the interfacial adhesion. Viscoelasticity and composite viscosity were improved after treating fibers or adding TGIC.